Copper- and ligand-free sonogashira reaction catalyzed by Pd(0) nanoparticles at ambient conditions under ultrasound irradiation - Gholap, Atul R.; Venkatesan, K.; Pasricha, R.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Journal of Organic Chemistry, 2005)
The Sonogashira reaction proceeds at ambient temperature (30 degrees C) in acetone or room-temperature ionic liquid, 1,3-di-n-butylimidazolium tetrafluoroborate ([bbim]BF4), as solvent under ultrasound irradiation to give enhanced reaction rates, excellent chemoselectivity, and high yields in the absence of a copper cocatalyst and a phosphine ligand. TEM analysis showed the formation of stable, crystalline, and polydispersed Pd(0) nanoparticles as catalyst for the reaction.

Novel one-pot synthesis of 2-Aryl-4(3H)-quinazolinones using room temperature ionic liquid as reaction medium as well as promoter - Potewar, T. M.; Nadaf, R. N.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Synthetic Communications, 2005)
An efficient one-pot synthesis of 2-aryl-4(3H)-quinazolinones from 2-amino benzamides and substituted benzoyl chlorides in a room temperature ionic liquid is described. Compared with the classical reaction conditions, this new synthetic method has the advantages of recyclability of ionic liquid, very good to excellent yields (78-92%), the absence of hazardous and expensive catalysts, and easy workup procedures giving rise to a process with minimum waste.
Keywords: 2-amino benzamide; 2-aryl-4(3H)-quinazolinones; benzoyl chlorides; Ionic liquid

Room temperature ionic liquid promoted improved and rapid synthesis of 2,4,5-triaryl imidazoles from aryl aldehydes and 1,2-diketones or alpha-hydroxyketone - Siddiqui, S. A.; Narkhede, U. C.; Palimkar, S. S.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Tetrahedron, 2005)
An improved and rapid one-pot synthesis of 2,4,5-triaryl imidazoles in a room temperature ionic liquid is described, which does not need any added catalyst. Different ionic liquids based on 1-n-butyl and 1,3-di-n-butyl imidazolium salts were screened and their efficacy in terms of acidity and polarity have been correlated with yields and reaction period. The one-pot methodology resulting in excellent isolated yields in short reaction times is characterized by simple work up procedures and efficient recovery and recycling of the ionic liquid, which acts as a promoter. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: 1; 2; 2-Diketones; 4; 5-triaryl imidazoles; alpha-hydroxyketone; ammonium acetate; benzaldehydes; ionic liquid (IL)

Remarkably rapid regioselective synthesis of beta-enaminones using silica chloride in a heterogeneous as well as an ionic liquid in a homogeneous medium at room temperature - Gholap, Atul R.; Chakor, N. S.; Daniel, Thomas; Lahoti, Rajgopal J.; Srinivasan, K. V. (Journal of Molecular Catalysis A-Chemical, 2006)
{Silica chloride as a heterogeneous catalyst has been used for the regioselective synthesis of P-amino-a,P unsaturated esters and ketones. Similar regioselective synthesis was also performed using an ionic liquid 1-n-butyl imidazolium tetrafluoroborate [
Keywords: direct oxidation of H-2 to H2O2; H2O2 decomposition; H2O2 hydrogenation; Promoting action of chloride or bromide anions; supported Pd catalysts

Efficient synthesis of 1,8-dioxo-octahydro-xanthene derivatives promoted by a room temperature ionic liquid at ambient conditions under ultrasound irradiation - Venkatesan, K.; Pujari, Suresh S.; Lahoti, Rajgopal J.; Srinivasan, K. V. (Ultrasonics Sonochemistry, 2008)
The condensation reaction involving an aldehyde and diketone was efficiently promoted by the Ionic liquid, [Hbim]BF(4) (IL) as a reaction medium with methanol as co-solvent at ambient temperature under ultrasonic irradiation to afford the corresponding 1,8-dioxo-octahydroxantliene (xanthene) derivatives in excellent yields. The advantages of this method include among others the use of a recyclable, non-volatile ionic liquid, which promotes this protocol under ambient temperature without the requirement of ally added catalyst. The reaction times and yields are compared with p-TSA catalyzed synthesis of xanthenes under thermal conditions, which is also reported for the first time under our reaction conditions. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: aldehydes; ambient conditions; Bronsted acidity; dimedone; Ionic liquid; Ultrasound; Xanthenes

Novel stereoselective synthesis of pachastrissamine (jaspine B) starting from 1-pentadecanol - Venkatesan, K.; Srinivasan, K. V. (Tetrahedron-Asymmetry, 2008)
A novel stereoselective synthesis of pachastrissamine (jaspine B), starting from commercially available 1-pentadecanol is described. Sharpless asymmetric dihydroxylation and a chelation controlled vinyl Grignard reaction are the key steps in this synthetic strategy. (C) 2007 Elsevier Ltd. All rights reserved.

Stereoselective synthesis of (S)-dapoxetine starting from trans-cinnamyl alcohol - Venkatesan, K.; Srinivasan, K. V. (Arkivoc, 2008)
A novel stereoselective synthesis of (S)-dapoxetine starting from commercially available trans-cinnamyl alcohol is described. Sharpless Asymmetric Epoxidation (SAE) is utilized as the key step in this synthetic strategy.
Keywords: (S)-dapoxetine; antidepressant; Sharpless asymmetric epoxidation; stereoselective synthesis

Design, synthesis and evaluation of unique 2,4,5-triaryl imidazole derivatives as novel potent aspartic protease inhibitors - Khan, Mohd Sajid; Akhtar, Salman; Siddiqui, S. A.; Siddiqui, M. S.; Srinivasan, K. V.; Arif, J. M. (Medicinal Chemistry, 2012)
The 2,4,5-triaryl imidazole derivatives (API) were designed, screened and characterized kinetically & thermo-dynamically against Pepsin and their activity was also tested on the in silico platform. The docking studies of API with Pepsin show that these are novel and unique inhibitors of Aspartic protease. Drug like properties of these compounds were validated in silico based on Lipinski's rule of Five by calculating ClogP, LogS, H-bond acceptors, H-Bond donors, rotational bonds, PSA, PB and BBB values. The Et/Ki and Et/Km values of API show that they follow the Michaelis-Menten kinetics. The binding of inhibitors with proteases was explained by using Van't Hoff plot and thermodynamic parameters viz. free energy (Delta G), Entropy (Delta S) and Enthalpy (Delta H). The Van't Hoff analysis showed that the value of K-i decreases with increase in temperature and the binding of the inhibitor are entropically driven. API act as new potent aspartic protease inhibitors with K-i, for Pepsin, ranges from 3.7 mu M to 16.7 mu M. Strong hydrophobic groups at C-4 & C-5 position in API favor binding of inhibitors with Pepsin. Experiments also showed that among C-2 aryl substituted imidazole, a 4-substitution on aryl ring is preferred and less polar substituent makes the molecule more active whereas polar substituents at 2-position on C-2 aryl ring makes the molecule less active. The docking studies of API with Pepsin further intensify and validate our results.
Keywords: 2; 4; 5-triaryl imidazole derivatives; docking; Lipinski's rule of Five; Protease inhibitors; Thermodynamics